Working Americans, 1880-2015. - Derks, Scott (Gale virtual reference library., 2015)
This volume examines the lives of Americans during wartime, including declared conflicts, one-time military actions, protests, and preparations for war. For each decade, several personal profiles tell the stories of civilians, soldiers, and officers.